Music and Neuroscience - Mara, Angelica; Laskari, Katia (Open Schools Journal for Open Science, 2025)
This presentation explores the relationship between music and neuroscience. It examines how music activates different brain regions, supports neuroplasticity, and contributes to therapeutic practices. Finally, it presents current and future applications of music therapy in cognitive and physical rehabilitation.